Intravascular Ultrasound-Guided Troubleshooting in a Large Hematoma Treated With Fenestration Using a Cutting Balloon - Noh, Hye Jin; Choi, Jin-Ho; Song, Young Bin; Jo, Hyun Chul; Yang, Ji Hyun; Kim, Sang Min; Lee, Hyun Jong; Choi, Joon Hyuk; Choi, Soo Hee; Hahn, Joo Yong; Choi, Seung Hyuk; Gwon, Hyeon Cheol (Korean circulation journal, 2009)
Intramural hematoma formation is not a well-studied complication of percutaneous coronary intervention. We describe a patient with stable angina who developed an intramural hematoma during elective percutaneous coronary intervention (PCI) in the right coronary artery (RCA). Total occlusion with dense dye staining developed a long way from the distal RCA, near the posterior descending artery bifurcation site. The true lumen was compressed by the enlarged, tense, false lumen. The patient was successfully treating with intravascular ultrasound-guided fenestration using a cutting balloon, and a stent was implanted in the distal RCA.